Assessing an inclusive model to increase access to comprehensive gender-based violence response services and improve HIV outcomes in Puerto Plata, Dominican Republic. Issue 9 (1st September 2020) - Dayton, Robyn; Alvarez, Betty; Morales, Giuliana J.; Rojas Almonte, Josefina; Faccini, Monica; Gomes, Bayardo; Wolf, R. Cameron; Wilcher, Rose
Abstract: Experiences of gender-based violence (GBV) are associated with increased vulnerability to HIV and difficulty accessing HIV services; at the same time, people living with HIV are at an increased risk of GBV. Key populations most affected by HIV – gay and other men who have sex with men, female sex workers and transgender women – also experience a disproportionate burden of GBV. In Puerto Plata, Dominican Republic, a local civil society organisation has led efforts to improve and integrate GBV and HIV services while making them welcoming to key population members and people living with HIV. According to interviews with service providers and service users and an analysis of service statistics, the intervention improved service quality and coordination, increased disclosures of violence and increased GBV response service uptake among the general population, key population members and people living with HIV. Findings also suggest that the intervention increased the uptake of HIV services, including HIV testing and post-exposure prophylaxis, and improved mental health among those receiving GBV response services. This case study of integrated GBV and HIV services describes a new model for simultaneously, synergistically and inclusively addressing two major epidemics negatively affecting health and well-being in affected communities today.